Development of Prezi-Based Video Media in Fine Arts Learning on Decorative Drawing Materials for Students of Grade VII of Junior High School 6 Padang - Rosalena Aprizia; Yofita Sandra (SAINTIS Publishing, 2025)
This study aims to develop Prezi-based video learning media in Fine Arts learning on Decorative Drawing material for grade VII students of Junior High School 6 Padang. This study is a development research or Research and Development (R D). The model used is the development of Borg Gall. The results of the study showed that the assessment results from language experts were 94.3%, the assessment results from material experts were 93.3%. The assessment results from media experts were 94% and the assessment results from teachers were 98%. This shows that Prezi-based video media is very feasible to use. The main field trial on the student questionnaire obtained 86% while the test results obtained 84%. The operational trial on the student questionnaire obtained 93.35%, while the test results obtained 91.2%. After being converted with an assessment scale, it shows that Prezi-based video media is very feasible to use. This shows that Prezi-based video media in Fine Arts lessons on Decorative Drawing material can improve student learning outcomes and is very suitable for use as a learning medium for students and teachers at State Junior High School 6 Padang.